تجسيد الشخصيات الإسلامية في الوسائط المتعددة : دراسة فقهية تحليلية - هاجري، مبارك محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2020)
This research discusses the issue of embodying and simulating Islamic Figures in multimedia from an Islamic jurisprudence perspective. The research attempts to highlight its impact on the beliefs, values, and behaviors of children, individuals, and societies. The researcher mentioned the purpose of multimedia and its types, defined Islamic figures and clarified the meaning of embodiment and simulation and their methods, and how Islamic figures have been embodied in multimedia. The researcher followed the inductive analytical method. He explored the relevant scientific research, gathered information, discuss it, and analyzed it. The importance of the research stems from the fact that it touches an issue that is permitted by the Almighty God, yet it has been misunderstood and misused. Multimedia is the most important mean of transferring information in this era. It has an impact on the individual and society, but it also affects the position of Islamic figures. One of the most important results of this research is that the embodiment of Islamic figures through multimedia preserves the beliefs and values of our children, in particular, increases their knowledge about Islamic history and their love for the prophets and companions. Moreover, to bring the best out of it, it is important to develop a legal framework to better monitor and control the embodiment of Islamic figures.